PENGARUH CORPORATE SOCIAL RESPONSIBILITY PADA KINERJA PERUSAHAAN MANUFAKTUR - Pramana, I Gede Aditya; Yadnyana, I Ketut (E-Jurnal Akuntansi, 2016)
Implementation of social responsibility (CSR) has been widely applied to various types of companies, including the non-profit corporation. This is because the implementation of CSR is able to affect the company's performance. This reasearchin on companies on the Stock Exchange period 2011-2013. Samples were taken deliberately so as much as 55 used as a sample. With a simple linear regression analysis obtained results of this study as follows, CSR disclosured significant impact on the return on assets (ROA) and the cumulative abnormal return (CAR). It means that CSR disclosure by the company will provide a positive and significant effects on the company's financial performances & the performance enterprise market. This means that with the penggungkapan CSR company, then chances, trespon positively by investors and many investors who invest in the company that led to the increased performance of the company.
Keywords: CSR, ROA, CAR